Study on the effects of upper respiratory tract infection, adenoid hypertrophy, and environmental factors on allergic rhinitis - Yang, Fengbo; Alhoot, Mohammed Abdelfatah (Edelweiss Applied Science and Technology, 2026)
To investigate the direct effects of Upper Respiratory Tract Infection and Adenoid Hypertrophy on Allergic Rhinitis, and to examine the mediating role of a harsh environment in these relationships, a quantitative cross-sectional study was conducted. Data were collected from 387 valid respondents using standardized questionnaires. Descriptive and correlation analyses were performed with SPSS 26.0, while AMOS 24.0 was used to construct a structural equation model to test both direct and mediating effects. Results showed that Upper Respiratory Tract Infection, Adenoid Hypertrophy, and a harsh environment each had significant direct positive effects on Allergic Rhinitis. Importantly, the harsh environment partially mediated the relationships between the two pathological factors (infection and hypertrophy) and Allergic Rhinitis. This suggests that these factors not only directly worsen the condition but also indirectly exacerbate it by increasing susceptibility or exposure in poor environmental conditions. The study confirms an interaction between individual pathological status and environmental factors in Allergic Rhinitis, establishing a combined pathway that amplifies disease severity. Prevention and treatment strategies should adopt an integrated medical and environmental approach. Clinically, proactive management of infections and hypertrophy is essential. At the public health level, improving environmental quality is fundamental to controlling the disease at its source.